Ecological∼Enactivism Through the Lens of Japanese Philosophy - McKinney, Jonathan (Frontiers in Psychology, 2020)
The enactive and ecological approaches to embodied cognitive science are on a collision course. While both draw inspiration from similar views in psychology and phenomenology, the two approaches initially held seemingly contradictory views and points of focus. Early enactivists saw value in the ecological approach but insisted that the two schools remain distinct. While ecological psychology challenged the common foes of mental representation and mind-body dualism, it seemingly did so at the cost of the autonomy of the agent. This is evidence that the early enactive and ecological approaches told different stories about how agents and environments interact. Whereas the enactive approach broadly focuses on agency and the organism’s resilience to environmental perturbations, the ecological approach insists that organisms are best understood in terms of the organism–environment system and at the ecological scale. Historically, this tension created space for harsh criticisms from both sides and for some ecological psychologists to dismiss enactivism altogether. Despite their differences, both approaches use dynamic systems theory to explain the interactions between embodied agents and the environment or contextual milieu in which they are embedded. This has led some scholars to focus on the complementary elements of each approach and argue that the two schools are allies, thus rejecting the historical disagreements between the two approaches and calling for an ecological–enactive synthesis. The attempts to synthesize the approaches are noteworthy and should be considered steps in the right direction but are potentially problematic. If the two schools are merely synthesized to some form of ecological–enactivism, then something of value from both approaches could be lost. This is analogous to the hasty comparison between two seemingly similar schools of thought found in early attempts at East-West comparative philosophy. I argue that the relationship between the enactive and ecological approaches is both complementary and contrary and is thus best understood in terms of complementarity. Given the complexity of complementarity I will unpack the notion in steps. I will begin with the exploration of analogous concepts in Japanese Philosophy and gradually build a lens through which both agent environment and ecological enactive complementarities can be understood.